Structure of many-level adaptive automatic voltage regulation system - Golikov I.O.; Vinogradov A.V.; Bolshev V.E.; Vinogradova A.V.; Jasinski M.; Gibadullin R.R. (E3S Web of Conferences, 2020)
This article describes the features of voltage regulation in electrical networks of 35, 110, 220 kV. The structural diagram of the 35/10/0.4 kV network is presented. The paper also describes the adaptive automatic voltage regulation system which allows regulating the voltage taking into account the actual voltage values at the consumers’ inputs. The structural diagram of the adaptive automatic voltage regulation system in the 0.4 kV electrical network using a boost transformer as an additional means of voltage regulation is given. The system is based on voltage sensors installed in different parts of an eletcrical network sending information on voltage values to to the processing unit which generates a signal for voltage regulating supplied to the executive device and the working body whuch, in turn, change the on-load tap-changer position of a transformer. The paper justifies the need for the enhancement of the adaptive automatic voltage regulation system for different voltage classes wich allows controlling a voltage change at different power supply system levels and regulating voltage level in accordance with this change. For this problem the multi-level adaptive automatic voltage regulation systemis proposed. The system allows regulating the voltage not only in the 0.4 kV network but also in networks of higher voltage classes. The proposed system can be integrated into the structure of intelligent electrical networks.